Coffee tree response to potassium fertilization in low and high yields - Silva, Enilson de Barros; Nogueira, Francisco Dias; Guimarães, Paulo Tácito Gontijo; Neto, Antônio Eduardo Furtini (Pesquisa Agropecuaria Brasileira, 2001)
In order to evaluate the response of coffee trees to potassium fertilization for low and high yield, two experiments were carried out in two Oxisols of Epamig Experimental Farms, in the Minas Gerais state, Brazil. The experiments were implanted in a field crop of the cultivar Catuaí Vermelho, line MG-99, which was planted six years ago at the spacing 3.5 x 0.7 m. The experiment was carried out in a randomized block design, with four repetitions in the split plot scheme. In the plots, K sources were applied: potassium chloride, potassium sulphate and potassium nitrate; and in the subplots, K doses (0, 100, 200 and 400 kg ha-1) were applied. Yield of processed coffee grains, available soil K (Mehlich-1) and leaf contents were determined in four crops (1995 to 1998): two crops for low yields (1995 and 1997) and two crops for high yields (1996 and 1998) in both soils. Coffee tree response to K doses was different between high and low yield. The yield alternation of coffee trees shows that critic levels of K in the soil and in the leaf contents should be obtained in high crops.